Dating Urban Classical Deposits: Approaches and Problems in Using Finds to Date Strata - Guido Furlan (Archaeopress Archaeology, 2019)
Dating Urban Classical Deposits: Approaches and problems in using finds to date strata considers the issues surrounding the dating of archaeological strata on the basis of the assemblages recovered from them. This process is one of the most common processes in archaeology, yet it is still poorly structured theoretically, methodologically and operatively. No manuals specifically tackle the issue as a whole and consideration of useful theoretical and methodological tools is fragmentary. This book has been developed to try to correct this failing; it is based on the idea that for dating a given layer through the materials recovered from it, the embedding process of the materials must be modelled. The book reviews the present state of archaeological practice and follows this with a theoretical discussion of the key concepts involved in the issue of dating deposits; the main methodological tools which can be employed (quantitative, qualitative and comparative) are then discussed in detail. The text presents a problem-oriented taxonomy of deposits, with depositional models for assessing how different assemblages can be analysed for dating; each type of deposit is accompanied by case studies where the methodological tools used are explained. Finally, a structured working method is proposed. The topic of dating deposits crosses the chronological and spatial borders of many archaeologies, but the book focusses on Classical cities (particularly Roman), as they present specific traits (continuous occupation, high rates of residuality, high impact architecture, waste management etc.) making them unique fields for study.